DEBATING THE SCIENCE OF JURISPRUDENCE: STUDYING JURISPRUDENCE FROM PHILOSOPHY OF SCIENCE PERSPECTIVE - Nur Ro'is (International Conference on Social and Islamic Studies, 2021)
The Article discusses jurisprudence in terms of the philosophy of science; so far, there havebeen doubts in the study of jurisprudence due to the object, whether jurisprudence is included inscience or only knowledge of legislation. In discussing jurisprudence, the author uses literaturesearch methodology (library research) using the Philosophy of Science approach, specificallyEpistemology, Ontology, and Axiology. The Philosophy of science approach will reveal themeaning of science on Jurisprudence.